The European company law action plan revisited : reassessment of the 2003 priorities of the European Commission - Geens, K. (Koen); Hopt, Klaus J., 1940- (Leuven University Press, 2010)
The harmonisation of company law has always been on the agenda of the European Union. Besides the protection of third parties affected by business transactions, the founders had two other objectives: first, promoting freedom of establishment, and second, preventing the abuse of such freedom. In fact, the fear of the Netherlands becoming the 'Delaware of Europe'' (in terms of competition among Member States) seemed real, until, ironically, at the beginning of the 21st century, it was the privilege of the Dutch (and the Danish) state to fail in making the abuse argument before the European Court.